The Double Track System Application Effectiveness Against Addictives And Drug Abusers In Purbalingga Regency - Arinda Intan Arditasari (Faculty of Law Universitas Muhammadiyah Purwokerto, 2022)
AbstractNarcotics is a great crime that significantly impacts the country, especially the nation's generation. Based on Narcotics Law Number 35 of 2009 concerning Narcotics, Narcotics are divided into three types: Narcotics, Psychotropics, and other addictive substances. The settlement of narcotics crimes is not only imprisonment but there are sanctions for rehabilitation measures for the category of narcotics users, namely addicts and narcotics abusers who are not narcotics dealers or couriers. This research aims to benefit the general public as a reference for written works after this and can provide solutions to existing problems. This study uses a normative juridical method with interviews with related parties. Researchers get results research that during 2020 there were addicts and narcotics abusers arrested in conditions that BNN Purbalingga Regency and Police Investigators arrested 30 people. Then an Integrated Assessment Test (TAT) was held by BNN. Of the 30 people, only two were ordered for rehabilitation, and the other 28 were only in prison. The results of the (TAT) are not used as a consideration to rehabilitate the suspect because the judge also sees the facts in court. There is no phrase